Metode Peer Lesson Dan Peer Tutor Dalam Meningkatkan Hasil Belajar Fiqih - Asmawi HM (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2019)
This study aims to: 1) Determine the effectiveness of the peer lesson method in improving the learning outcomes of jurisprudence of class X students at Madrasah Aliyah Darul Hikmah Kedungmaling Sooko Mojokerto, 2) Knowing the effectiveness of the peer tutor method in improving the learning outcomes of class X students in Islamic schools of Aliyah Darul Hikmah Kedungmaling, Kedungmaling Sooko Mojokerto. This type of research is quantitative-comparative. Data collection techniques using questionnaires, interviews, documentation and tests. The population in this study was 131 students of class X MA. Darul Hikmah Kedungmaling Sooko Mojokerto. Researchers took a sample of 40 students randomly. The data analysis technique uses statistical correlation coefficient analysis. Hypothesis testing shows that: 1) The peer lesson method is effectively used in improving the fiqh subjects of class X students in the MA. Darul Hikmah Kedungmaling Sooko Mojokerto. This is indicated by a correlation value of 0.800 which indicates a high relationship or influence between the peer lesson method and student learning outcomes.